1996
DOI: 10.1007/s002530050663
|View full text |Cite
|
Sign up to set email alerts
|

Killing of microorganisms by pulsed electric fields

Abstract: Lethal effects of pulsed electric fields (PEF) on suspensions of various bacteria, yeast, and spores in buffer solutions and liquid foodstuffs were examined. Living-cell counts of vegetative cell types were reduced by PEF treatment by up to more than four orders of magnitude (> 99.99%). On the other hand, endo- and ascospores were not inactivated or killed to any great extent. The killing of vegetative cell types depends on the electrical field strength of the pulses and on the treatment time (the product of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
225
4
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(249 citation statements)
references
References 24 publications
10
225
4
6
Order By: Relevance
“…It can therefore be concluded that PEF processing of milk may involve modifications of its structure because functional properties such as cheese-making properties are modified by the treatment. These results are not in agreement with some other studies reporting that PEF treatment preserves the nutritional components and minimizes physical and chemical changes in food products [9,14,24]. Michalac et al [21] measured that total solids, protein, pH, electrical conductivity, viscosity and density of milk were not affected by PEF processing.…”
Section: Casein Micelles Characteristicscontrasting
confidence: 53%
See 1 more Smart Citation
“…It can therefore be concluded that PEF processing of milk may involve modifications of its structure because functional properties such as cheese-making properties are modified by the treatment. These results are not in agreement with some other studies reporting that PEF treatment preserves the nutritional components and minimizes physical and chemical changes in food products [9,14,24]. Michalac et al [21] measured that total solids, protein, pH, electrical conductivity, viscosity and density of milk were not affected by PEF processing.…”
Section: Casein Micelles Characteristicscontrasting
confidence: 53%
“…Color and particle sizes of the milk were not changed significantly by this processing. Only Grahl and Märkl [14] measured some PEF-induced destruction of milk components, but only at high energy inputs (Q > 200 kJ·kg -1 ) for the enzyme lipase and vitamin C (ascorbic acid). Other food components that were analyzed (alkaline phosphatase, peroxidase, vitamin A and whey protein) did not show any large-scale inactivation.…”
Section: Casein Micelles Characteristicsmentioning
confidence: 99%
“…Additionally, electromagnetic waves induced great reduction in viable cells of microorganisms depending on the wave frequency, time of exposure and/or the exposed organism (Grahl and Markl, 1996). Such reduction might be due to breakdown of cell membrane (Calderon-Miranda et al, 1999;Schoenbach et al, 2000;Dunne, 2000;Oshima and Sato, 2004;Aronsson et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…8 Nas reações que ocorrem com a passagem da corrente elétrica nos eletrodos são gerados vários componentes tóxicos à viabilidade celular. 9 O objetivo deste trabalho foi utilizar o tratamento eletrolítico na água proveniente do Rio das Cinzas, Bandeirantes -PR, avaliando a possibilidade da retirada do gás cloro utilizado no pré-tratamento da água bruta, na ETA do Serviço Autônomo de Água e Esgoto (SAAE), onde numa primeira fase foram testados o processo eletrolítico e coadjuvantes do tratamento tradicional de água. Finalmente, buscou-se avaliar a geração de substâncias tóxicas pelo processo eletrolítico aplicado através de testes de biotoxicidade aguda com o microcrustáceo Daphnia similis.…”
Section: Introductionunclassified